Rock Water as a Key Resource for Patchy Ecosystems on Shallow Soils: Digging Deep Tree Clumps Subsidize Surrounding Surficial Grass. Issue 2 (12th February 2021) - Montaldo, Nicola; Corona, Roberto; Curreli, Matteo; Sirigu, Serena; Piroddi, Luca; Oren, Ram
Abstract: Mediterranean mountainous areas of shallow soil often display a mosaic of tree clumps surrounded by grass. The combined role and dynamics of water extracted from the underlying rock, and the competition between adjacent patches of trees and grass, has not been investigated. We quantified the role rock water plays in the seasonal dynamics of evapotranspiration ( ET ), over a patchy landscape in the context of current and past seasonal climate changes, and land‐cover change strategies. Soil water budget suggests deep water uptake by roots of trees (0.8–0.9 mm/d), penetrating into the fractured basalt, subsidized grass transpiration in spring through hydraulic redistribution. However, in summer trees used all the rock water absorbed (0.79 mm/d). A 15‐year data set shows that, with increasing seasonal drought‐severity (potential ET /precipitation) to >1.04, the vertical water flux through the bottom of the thin soil layer transitions from drainage to uptake in support of ET . A hypothetical grass‐covered landscape, with no access to deep water, would require 0.68–0.85 mm/d more than is available, forcing shortened growing season and/or reduced leaf area. Long‐term decreasing winter precipitation and increasing spring potential ET suggest drying climate, so far with stable vegetation mosaic but progressively earlier peak of grass leaf area. Intervention policies to increase water yield by reducing tree cover will curtail grass access to rock moisture, while attempting to increase tree‐related products (including carbon sequestration) by increasing forest cover will limit water availability per tree leaf area. Both changes may further reduce ecosystem stability. Plain Language Summary: In drier regions, individual trees or tree clumps are often surrounded by seasonal vegetation. Increasing climatic drought, form decreasing precipitation in winter and increasing potential evapotranspiration in spring, is common in these regions. Where the balance among vegetation types in a mosaic depends on deep water to subsidize transpiration, increasing drought may overwhelm the capacity for this subsidy, affecting both land cover and biosphere‐atmosphere exchanges. Here we show that, in patchy ecosystems, nighttime hydraulic‐lift of rock‐moisture by wild‐olive roots recharges the shallow soil, enough to support transpiration of grass and trees in spring, but only trees in summer. Thus, seasonal vegetation rely on the evergreen trees to maintain physiological activity in spring, while the evergreen trees rely on the inactivity of the seasonal component to maintain their own activity in the dry season. These ecosystems likely represent a spatiotemporal equilibrium of water supply, dynamically meeting the demand of two adjacent vegetation types of distinct seasonal phenology. The equilibrium is not only highly sensitive to climate change, but may be destabilized by policies aiming to increase carbon sequestration by increasing tree cover, or water yield by increasing seasonal vegetation cover, with additional consequences to decreasing tree survival or increasing surface temperature Key Points: In patchy ecosystems, nighttime hydraulic‐lift of rock‐moisture by wild‐olive roots recharges the shallow soil supporting transpiration The water balance of patchy semi‐arid ecosystem is highly sensitive to climate change